N-Methyl-D-Aspartate Receptor Antibodies in Herpes Simplex Encephalitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Researchers at Charite University Medicine Berlin, and other centers in Germany, Spain and the US performed a retrospective analysis of 44 patients with polymerase chain reaction-proven herpes simplex encephalitis (HSE) for the presence of onconeuronal and synaptic receptor antibodies.